Georgia : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2004)
The staff report for the Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility on Georgia focuses on economic developments and policies. The fiscal situation deteriorated sharply in 2003, especially because of a weakening in expenditure management and in tax enforcement. Policy discussions focused on strategies to address the challenges inherited from the previous administration and to reinvigorate the reform drive. Georgia's vulnerability to exogenous shocks and lingering tensions between central and regional authorities will continue to pose downward risks.